The database on oceanography of the eastern Okhotsk Sea - V. V. Kolomeytsev; S. L. Gorin (Известия ТИНРО, 2023)
Database for the data of oceanographic observations in the eastern part of the Okhotsk Sea (on the shelf of West Kamchatka and in adjacent waters) obtained in 1888–2020 is created in KamchatNIRO (Petropavlovsk-Kamchatsky) that introduces many previously inaccessible data into scientific circulation and thus provides new possibilities for exploration of this area. The database is heterogeneous in its temporal and spatial resolution. The 1961–1990 period is better covered by the data, whereas the observations in the last three decades (1991–2020) are slightly less numerous. Spatial density of observations increases from the open sea to the coast and from the north to the south; the densest net of stations is located at the southwestern coast of Kamchatka.